Alpha‐ and beta‐mannan utilization by marine Bacteroidetes. (16th October 2018) - Chen, Jing; Robb, Craig S.; Unfried, Frank; Kappelmann, Lennart; Markert, Stephanie; Song, Tao; Harder, Jens; Avcı, Burak; Becher, Dörte; Xie, Ping; Amann, Rudolf I.; Hehemann, Jan‐Hendrik; et al.
Summary: Marine microscopic algae carry out about half of the global carbon dioxide fixation into organic matter. They provide organic substrates for marine microbes such as members of the Bacteroidetes that degrade algal polysaccharides using carbohydrate‐active enzymes (CAZymes). In Bacteroidetes genomes CAZyme encoding genes are mostly grouped in distinct regions termed polysaccharide utilization loci (PULs). While some studies have shown involvement of PULs in the degradation of algal polysaccharides, the specific substrates are for the most part still unknown. We investigated four marine Bacteroidetes isolated from the southern North Sea that harbour putative mannan‐specific PULs. These PULs are similarly organized as PULs in human gut Bacteroides that digest α‐ and β‐mannans from yeasts and plants respectively. Using proteomics and defined growth experiments with polysaccharides as sole carbon sources we could show that the investigated marine Bacteroidetes express the predicted functional proteins required for α‐ and β‐mannan degradation. Our data suggest that algal mannans play an as yet unknown important role in the marine carbon cycle, and that biochemical principles established for gut or terrestrial microbes also apply to marine bacteria, even though their PULs are evolutionarily distant.